Community Legal Compliance With Regulations For The Prevention And Handling of COVID-19 - Kasim, Aminuddin; Suarayasa, Ketut; Syamsuddin, Adiesty Septhiany (Widya Yuridika, 2023)
Legal compliance in the community is always an interesting issue to discuss. The research question in this study is how the compliance of the members of the Tadulako University academic community in response to the Decree of the Minister of Health of the Republic of Indonesia Number: HK.01.07/MENKES/413/2020 concerning Guidelines for the Prevention and Control of COVID-19 through the implementation of Tracing, Testing, and Treatment (3T Program)? To answer the research objectives, empirical legal research (socio-legal research) was conducted to support the depth of analysis. The analysis materials include data on the conditions and levels of health risks experienced by the academic community based on the available COVID-19 link records, data on the number and distribution of academic community members who have been infected with COVID-19, and data on the implementation of the 3T program sourced from Tadulako Hospital. Starting from the interpretation of the research data analysis, the findings revealed: (a) there are some members of the academic community who do not respond to filling in data regarding the condition and level of health risk on the available COVID-19 link; (b) members of the academic community who have had a history of contact with COVID-19 sufferers have not all complied with the rules for preventing and handling COVID-19 through the implementation of 3T; (c) members of the academic community who are declared positive for COVID-19 infection have relatively high legal compliance in supporting the implementation of treatment. Their legal compliance is categorized as identification according to Herbert C. Kelman’s theory.